Developing a Muhammadiyah Institutional Resilience Framework (MIRF): Integrating Academic Excellence, Financial Sustainability, Digital Transformation, Governance, and Islamic Values for Sustainable Higher Education - Elihami Elihami (Al-Mirah: Jurnal Pendidikan Islam, 2026)
This study develops the Muhammadiyah Institutional Resilience Framework (MIRF), a multidimensional model designed to strengthen the sustainability and competitiveness of Islamic higher education institutions in the era of digital disruption and global competition. The framework integrates six strategic dimensions: academic excellence, financial sustainability, human resource development, digital transformation, governance resilience, and Muhammadiyah Islamic values. The study is motivated by the growing need for universities to move beyond traditional performance indicators and adopt a holistic resilience-oriented governance model that can respond adaptively to crises, policy changes, technological shifts, and societal demands. Using a qualitative-conceptual approach supported by literature review and institutional analysis, the study synthesizes theories of organizational resilience, higher education governance, digital transformation, and Islamic educational values. The resulting MIRF proposes that institutional sustainability is achieved when academic quality, financial health, technological readiness, effective governance, and value-based leadership operate in an integrated manner. Muhammadiyah values such as integrity, social responsibility, innovation, and service to society function as the ethical foundation that aligns organizational resilience with the broader mission of Islamic education. The framework contributes to the literature on higher education management by offering a context-sensitive model for Islamic universities, particularly within the Muhammadiyah network. Practically, MIRF can serve as a strategic planning tool, an institutional evaluation instrument, and an early warning system for assessing university resilience. The study also proposes the development of an Institutional Resilience Index to operationalize the framework in future empirical research. By combining managerial and spiritual dimensions, MIRF provides a comprehensive approach to building sustainable, adaptive, and value-driven higher education institutions.